2019
DOI: 10.1111/1753-6405.12910
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of surveillance data show late presentation among a diverse group of women diagnosed with HIV in Victoria, Australia

Abstract: Objective: To develop an HIV response suited to women and to inform appropriate services, we describe the characteristics of women diagnosed and living with HIV using 22 years of high‐quality surveillance data. Methods: Data on women newly diagnosed with HIV between 1994 and 2016 and women living with diagnosed HIV in Victoria at 31 December 2016 were extracted from the Victorian Public Health Surveillance System. Descriptive analysis by place of birth was performed and Poisson regression used to assess trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In Australia, the focus on HIV as predominately affecting MSM has meant heterosexual females and heterosexual males may fall outside the routine screening, be less likely to share their HIV status with healthcare providers outside of their main HIV medical service, and, therefore, miss the opportunity for timely and regular interventions [7,15]. A longitudinal study conducted in middle-income and high-income countries identified higher rates of non-retention in care among heterosexual males, opening the door for poorer virus control and potentially poorer overall health [7].…”
Section: Access To Medical Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, the focus on HIV as predominately affecting MSM has meant heterosexual females and heterosexual males may fall outside the routine screening, be less likely to share their HIV status with healthcare providers outside of their main HIV medical service, and, therefore, miss the opportunity for timely and regular interventions [7,15]. A longitudinal study conducted in middle-income and high-income countries identified higher rates of non-retention in care among heterosexual males, opening the door for poorer virus control and potentially poorer overall health [7].…”
Section: Access To Medical Servicesmentioning
confidence: 99%
“…Findings from this international study also identified more differences existed between heterosexual males and MSM than between heterosexual males and women in a number of health-related outcomes. In Australia, there is evidence that women's reduced visibility and potential reluctance to engage in medical services and social networks that focus on, and are frequented by, MSM, the largest HIV group, means they are more likely to feel isolated and 'slip through the cracks' medically and socially [15].…”
Section: Access To Medical Servicesmentioning
confidence: 99%
“… 2 The HIV Futures 9 Survey report 3 highlighted that women and men living with HIV have very different experiences. The disparities primarily concern service distribution and that many women living with HIV also carry a carer role 4 and may experience more stigma than men do when they acquire an HIV diagnosis, which can affect their social relationships and moral identity. 5–7 Women are at higher risk of acquiring HIV than is often acknowledged, as crucial factors in transmission risk include a complex mix of biological susceptibilities and socioeconomic and epidemiological factors.…”
Section: Introductionmentioning
confidence: 99%
“…About 3,000 women currently live with HIV in Australia, 14 representing ∼10% of the total population of Australians diagnosed with HIV. 4 It was estimated in 2020 that between 400 and 500 women living with HIV were unaware of their status. 15 In Victoria, between 1994 and 2016, there were 465 newly diagnosed women living with HIV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation